2003
DOI: 10.1086/379299
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation and Asymmetry in the Spiral Arms of M51: Variable Star Formation Caused by More than One Spiral Density Wave

Abstract: In the inner 3 kpc of M51, we find that logarithmic spirals provide good fits to the peak intensities in molecular gas observed by the Berkeley-Illinois-Maryland Association array in the CO (J = 1-0) emission line along the spiral arms. However, we measure significant asymmetries between the location and density of the arms observed on one side of the galaxy compared with those on the opposite side. Between a radius of 1 and 2.2 kpc, the gas distribution traced in CO is lopsided with densities twice as large i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 18 publications
10
39
0
Order By: Relevance
“…This trend is also reflected in the presence of large, isolated, and young star cluster complexes located in the west spiral arm, which appear to be absent on the east side of the galaxy. This is also consistent with the estimated star formation rates of Henry et al (2003). 5.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This trend is also reflected in the presence of large, isolated, and young star cluster complexes located in the west spiral arm, which appear to be absent on the east side of the galaxy. This is also consistent with the estimated star formation rates of Henry et al (2003). 5.…”
Section: Discussionsupporting
confidence: 91%
“…The higher cluster formation rate on the west side of the galaxy is also reflected in the presence of large, isolated and young star cluster complexes located in the western spiral arms, that appear to be largely absent in the eastern spiral arms . These complexes are typically less than ∼6 Myr old, contain 3 × 10 4 to 3 × 10 5 M , and are associated with large concentrations of CO (Henry et al 2003). Henry et al (2003) studied the present day star formation rate (SFR) and its relation to the molecular cloud content in the spiral arms of M 51, based on NICMOS (Paα) and BIMA-SONG (CO 1−0) observations.…”
Section: Duration Of the Burstmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, the cluster will also experience additional external perturbations, for example, the encounters with molecular clouds. The clusters in our sample are in the inner 5 kpc of the galaxy, where most of the giant molecular clouds reside (Henry et al 2003;Kuno et al 1995). The encounters with molecular clouds can speed up the disruption of clouds significantly (e.g.…”
Section: Implication Of the Derived Disruption Timementioning
confidence: 95%
“…Rand & Kulkarni (1990), Scoville et al (2001), and Tosaki et al (2002) noted that the Hα arms are located outside the CO arms. Henry et al (2003) found that the Paschen-α line emission is offset from the CO emission along part of the arms. All these shifts refer to the inner spiral system and are expected for arms triggered by density waves.…”
Section: Introductionmentioning
confidence: 96%